Contrast Sensitivity on 1/f Noise Is More Greatly Impacted by Older Age for the Fovea Than Parafovea. Issue 4 (April 2021) - Srinivasan, Rekha; Turpin, Andrew; McKendrick, Allison M.
Abstract : SIGNIFICANCE: Contrast sensitivity changes across the visual field with age and is often measured clinically with various forms of perimetry on plain backgrounds. In daily life, the visual scene is more complicated, and therefore, the standard clinical measures of contrast sensitivity may not predict a patient's visual experience in more natural environments. PURPOSE: This study aims to determine whether contrast thresholds in older adults are different from younger adults when measured on a 1/f noise background (a nonuniform background whose spatial frequency content is similar to those present in the natural vision environments). METHODS: Twenty younger (age range, 20 to 35 years) and 20 older adults (age range, 61 to 79 years) with normal ocular health were recruited. Contrast thresholds were measured for a Gabor patch of 6 cycles per degree (sine wave grating masked by a Gaussian envelope of standard deviation 0.17°) presented on 1/f noise background (root-mean-square contrast, 0.05 and 0.20) that subtended 15° diameter of the central visual field. The stimulus was presented at four eccentricities (0°, 2°, 4°, and 6°) along the 45° meridian in the noise background, and nine contrast levels were tested at each eccentricity. The proportion of correct responses for detecting the target at each eccentricity was obtained, and psychometric functions were fit to estimate the contrast threshold. RESULTS: Older adults demonstrate increased contrast thresholds compared with younger adults. There was an eccentricity-dependent interaction with age, with the difference between groups being highest in the fovea compared with other eccentricities. Performance was similar for the two noise backgrounds tested. CONCLUSIONS: Our results revealed a strong eccentricity dependence in performance between older and younger adults, highlighting age-related differences in the contrast detection mechanisms between fovea and parafovea for stimuli presented on nonuniform backgrounds. Abstract : Supplemental digital content is available in the text.